2018
DOI: 10.1016/j.celrep.2018.10.088
|View full text |Cite
|
Sign up to set email alerts
|

A Dock-and-Lock Mechanism Clusters ADAM10 at Cell-Cell Junctions to Promote α-Toxin Cytotoxicity

Abstract: Highlights d The a-toxin receptor ADAM10 is clustered at junctions by the PLEKHA7-PDZD11 complex d Tspan33 docks ADAM10 to junctions by binding to the WW domain of PLEKHA7 d ADAM10 junctional clustering promotes the efficient formation of stable toxin pores d Loss of PLEKHA7-PDZD11 leads to toxin pore removal by endocytosis and cell survival

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
73
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 43 publications
(77 citation statements)
references
References 64 publications
3
73
1
Order By: Relevance
“…Thus, Tspan15 and ADAM10 appear to be each required for the normal expression of the other. Indeed, it is well established that TspanC8s are important for ADAM10 maturation and trafficking to the cell surface (Dornier et al 2012; Haining et al 2012; Prox et al 2012; Zhou et al 2014; Jouannet et al 2016; Noy et al 2016; Virreira Winter et al 2016; Reyat et al 2017; Brummer et al 2018; Seipold et al 2018; Shah et al 2018; Brummer et al 2019), and we extended these observations by showing that ADAM10 surface expression was partially reduced in the absence of Tspan15 in A549, HEK-293T and HUVECs. Expression of other TspanC8s by these cells (Haining et al 2012; Matthews et al 2017) is likely to be the reason that the reduction is only partial.…”
Section: Discussionsupporting
confidence: 66%
“…Thus, Tspan15 and ADAM10 appear to be each required for the normal expression of the other. Indeed, it is well established that TspanC8s are important for ADAM10 maturation and trafficking to the cell surface (Dornier et al 2012; Haining et al 2012; Prox et al 2012; Zhou et al 2014; Jouannet et al 2016; Noy et al 2016; Virreira Winter et al 2016; Reyat et al 2017; Brummer et al 2018; Seipold et al 2018; Shah et al 2018; Brummer et al 2019), and we extended these observations by showing that ADAM10 surface expression was partially reduced in the absence of Tspan15 in A549, HEK-293T and HUVECs. Expression of other TspanC8s by these cells (Haining et al 2012; Matthews et al 2017) is likely to be the reason that the reduction is only partial.…”
Section: Discussionsupporting
confidence: 66%
“…By GST pulldown analysis, the N-terminal region of PLEKHA7 binds weakly to the C-terminal region of Tspan33, but this interaction is greatly enhanced in the presence of PDZD11 (13). In agreement, PDZD11 is required in cells for the interaction of PLEKHA7 with Tspan33, and clustering of the Tspan33-ADAM10 complex at junctions (13).…”
Section: Pdzd11 Promotes the Interaction Of Tspan33 With Plekha7 By Imentioning
confidence: 75%
“…ADAM10 is a transmembrane protease that cleaves extracellular regions of several transmembrane target proteins, including Notch . Furthermore, other Tspans have been shown to regulate ADAM10 maturation and activity, and Tspan3 itself has been shown to regulate ADAM10 expression . Our studies show that the Cldn‐11 effect on Notch signaling may be mediated via Tspan3 regulation of ADAM10 function.…”
Section: Discussionmentioning
confidence: 66%
“…ADAM10 is a transmembrane protein that cleaves extracellular regions of several transmembrane target proteins, including Notch, and we previously showed that osteoblasts express ADAM10 . Further, it was recently found that mutation of Tspan14 reduced ADAM10 surface expression and activity in human umbilical vein endothelial cells, and a number of other Tspans, including Tspan5, Tspan10, Tspan15, Tspan17, and Tspan33, have been shown to regulate ADAM10 activity . Notably, Tspan3 has also been found to regulate ADAM10 expression .…”
Section: Resultsmentioning
confidence: 93%